DEVELOPING OF SALES ACCOUNTING MODEL HOTEL SUPPLIER ON GROWTH OF BUSINESS REVENUE - Aryaningsih Ni Nyoman; Putu Rany Wedasuari; Made Bagiada; IGA Oka Sudiadnyani (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2019)
The growth of Hotel's business market share in Bali province is 10% for the last 5 years, when viewed from demand side. This condition as an indication of hotel business in Bali is still moving to grow-flower, so it needs a variety of efforts to boost sales turnover of the business. The supply side of Bali's business ventures is faced with business risk and natural risk or business tipping point, as indicated by trade, hotel and restaurant sector at -8.75%. This research is important to make efforts to realize the strategic plan of Bali State of Polytechnic that is Sustainability Green Tourism. The purpose of this research is to study the development of accounting model of hotel supplier's sales and business growth, and to analyze the impact of development of accounting model of hotel supplier's sales to the growth of business result. Data collection used survey method, in-depth interview and documentation. Data were analyzed descriptive statistics and Geometric index. The research findings show that the sales accounting model uses the time system block. The business risks faced by hotel suppliers are the change of human resource recruitment and replacement, so that the supplier relations of the hotel become disrupted. The growth rate of sales turnover tends to decrease due to natural and business risks.